Improvement of the performance of a coke drum operation using a computational fluid dynamic perspective (2017)
The delayed coking process is used in petrochemical industry for upgrading heavy crude oils such as residues from vacuum towers or Vacuum Residue Crude (VRC) and atmospheric bottoms. A delayed coking unit has three main parts: a fractionation tower, a furnace and a coke drum (reactor) in which the residue is converted into valuable products. The coke drum operates like an adiabatic semi-batch reactor and thermal cracking reactions are carried out inside the reactor. The coke drum is the main part of the process, it is important to identify possible bottlenecks and improve the performance of the coke drum operation. The selection of the main bottlenecks was carried out taking into account the most relevant process reported in industry. The source of that information could be: surveys in which representatives from some refineries discuss relevant issues and problems related to the coke drum, gray literature that describes operational problems in the delayed coking process and academic literature with a description of some problems of the delayed coking process, mainly for the coke drum. According to literature review, one of the most important bottlenecks is the plug of the vapor line. The possible routes for coke formation are condensation of high boiling point components, chemical reaction and mechanical deposition of coke. The three routes were evaluated and according to this, it was determined that there is not coke formation by condensation or chemical reaction.To evaluate the coke formation because of particles and drops shift, a CFD simulation was carried out. For CFD simulation it is important to know some physical properties of the compounds. To obtain this properties a simulation was carried out using the Delayed Coker Model from Aspen Hysys. A possible coke formation in the vapor line because of drops shift was obtained as result of the CFD simulation. To avoid the coke formation because of drops shift for a base case (tube at level with the reactor’s surface), a modification of vapor line was proposed. This modification consists in introduce a section of vapor line into the reactor. To define the relevance of this modification, two cases were evaluated: the introduction of the vapor line 30 cm and 3 m. According to these modifications, the introduction of the tube implies a reduction of the coke deposition. However, there is not a significant diference between the first case (30 cm) and the second one (3 m). To trying improve the above mentioned results, a geometry modification was proposed. It consists in modify the diameter of the coke drum at the top to increase the cross area and reduce the particle velocity which it is possible to delay the deposition of the particles. However, this alternative does not improve the previous results, by contrast, the coke deposition increased for the new geometry. Resumen El proceso de coquizaci´on lenta es usado en la industria petroqu´ımica con el fin de refinar crudos pesados tales como residuos provenientes de las torres de vac´ıo (VRC) y los fondos de las torres atmosf´ericas. Una unidad de coquizaci´on lenta consta de tres partes principalmente: una torre fraccionadora, un horno de precalentamiento y un par de reactores (drums) en los cuales el residuo se convierte en productos m´as livianos. Los drums operan como reactores semi-batch donde se llevan a cabo reacciones de craqueo. El drum es la parte m´as importante de este proceso, por tanto, es importante identificar posibles “cuellos de botella” y mejorar el rendimiento de la operaci´on del drum. Los posibles “cuellos de botella” la evaluaci´on de los posibles cuellos de botella se realiz´o teniendo en cuenta los problemas m´as relevantes reportados en la industria petroqu´ımica. La fuente de dicha informaci´on fue tomada de encuestas, en las cuales representantes de algunas refiner´ıas discuten sobre cuestiones relevantes y problemas relacionadas con el proceso; “literatura gris” en la cual se describen algunos problemas en la operaci´on del proceso en cuesti´on y literatura acad´emica con la descripci´on de algunos problemas del proceso de coquizaci´on lenta, principalmente en los drums. De acuerdo con la revisi´on de literature, uno de los principales “cuellos de botella” es el taponamiento de la linea de vapor debido a la formaci´on de coque. Las posibles rutas para la formaci´on de coque son: condensaci´on de componentes con alto punto de ebullici´on, formaci´on de coque por reacci´on qu´ımica y la deposici´on mec´anica de part´ıculas semicoquizadas. Las tres rutas fueron evaluadas y se obtuvo que para los casos de condensaci´on y de reacc´on qu´ımica no hay producci´on de coque. Para evaluar la formaci´on de coque debido al arrastre de gotas y part´ıculas, una simulaci´on CFD (Computational Fluid Dynamics) fue llevada a cabo. Para realizar una simulaci´on CFD es importante conocer algunas propiedades de los componentes que intervienen en el proceso, para esto se realiz´o una simulaci´on utilizando el Delayed Coker Model de Aspen Hysys. Para el caso de arrastre de gotas, se realiz´o una simulaci´on CFD y se encontr´o que es posible la formaci´on de coque en la linea de vapor dado un caso base (conducto de salida al nivel de la superficie del reactor). Para evitar el ensuciamiento del conducto de salida se propusieron algunos cambios en la linea de vapor, los cuales consisten en introducir un fragmento del conducto al interior del reactor. Para definir la pertinencia de estas modificaciones se propusieron dos casos: introducir el conducto 30 cm y 3 m. De acuerdo con esto, se encontr´o que las modificaciones propuestas implican una disminuci´on de la formaci´on de coque. Sin embargo, no existe una diferencia muy grande entre el primer caso (30 cm) y el segundo (3 m). Resumen IV Para intentar mejorar los resultados anteriores, se propuso un cambio en la geometr´ıa del reactor, la cual consiste en incrementar el di´ametro del reactor en la parte superior con el fin de reducir la velocidad de las part´ıculas lo cual puede generar un retraso en la deposici´on de ´estas. Sin embargo, esta alternativa no mejora los resultados anteriores, sino que por el contrario incrementa la deposici´on de coque.